Some socio-demographic and medical-anamnestic features of veterans with PTSD and TBI - Smashna Олена (Psychosomatic Medicine and General Practice, 2020)
Objective. Veterans’ mental health has been the subject of extensive research in many parts of the world. Particular attention is paid to PTSD, including in combination with trauma. Such comorbid conditions have a significant negative psychosocial impact, reducing the possibility of successful adaptation and resocialization of veterans. Certain features of socio-demographic and medical-anamnestic characteristics of veterans with PTSD, comorbid with TBI, as well as their problematic perception of certain areas of their lives may affect the formation of mental disorders, the course, and prognosis, success of therapy and rehabilitation, as well as recovery and quality of life. Thus, there is a need to study the characteristics of socio-demographic and medical-anamnestic characteristics of veterans with PTSD, especially in combination with CHD, to optimize pharmacological treatment and psychosocial therapy. Purpose: to investigate the socio-demographic, medical, and anamnestic characteristics of veterans with PTSD and CHD. Methods and materials. 329 combatants (members of the Armed Forces, the National Guard, and "volunteer battalions") in Eastern Ukraine who suffered from PTSD and LCHMT were examined. The socio-demographic and medical-anamnestic examination was performed using the Unified map of patient research developed by us. Results. Analysis of the socio-demographic characteristics of patients with PTSD and TBI shows that about a third of those surveyed gained primary adult life experience in a military conflict. Stay in the combat zone affected the work history: before entering the service in the ATO, most of the surveyed persons worked full time in the civilian sphere, and after being in the ATO, these figures decreased by more than 3 times due to redistribution in the category of those who continued to serve. The large number of people who continued to serve despite receiving PTSD, TBI, or a combination of these can be partly explained by the desire to maintain "fraternal unity" as a surrogate family. Most of the subjects were premorbidly psychosomatically healthy despite periodic alcohol consumption; somatic vulnerability was unique to TBI individuals. Conclusions. The socio-demographic, medical, and anamnestic features of veterans with PTSD and LCHMT identified by us were further used to form targets for psychosocial therapy and optimize pharmacological treatment.